Cyber Stalking Among Higher Secondary School Students in Kerala - Chandran, Anjana V. R; Raj. TX, Sundara (Indian Journal of Educational Technology, 2020)
Social Medias like Facebook, YouTube and Twitter have turned our life online and offline. Younger generations, particularly students are the predominant users of social networks. People can easily access the internet and social media applications from many different doorways. Social networking has become a salient feature of social life. Social networking sites are one of the most important means of communication among students. Most of them are not aware of the fact that how posting something improper can harm their security. The present study investigates the victimising cyber stalking of higher secondary school students and its relation with gender, frequency of login into cyber media and period of using social media. Data collected from 160 higher secondary school students using social media have been analysed with the help of the cyber stalking scale. Independent sample t-test, ANOVA and Chi-square tests were used to test the significance of difference. Study reveals that cyber stalking among higher secondary school students is high and there is no significant difference in the cyber stalking based on the frequency of login cyber media and duration of using social media, but difference is seen based on gender.